Hubungan Kepatuhan Perawat Menjalankan Standard Operational Procedure (SOP) Obat High Alert dengan Kejadian Medication Error di Rumah Sakit Dewi Sri Karawang - YAHYA SYUKRIA, YS (2021)
Medication errors are errors that occur during the treatment or treatment process that are at risk of causing harm to patients and their families. Nurses who do not comply with recommendations or a standard operating procedure (SOP) can cause errors in treatment. The purpose of this study was to analyze the relationship between nurses' adherence to standard operating procedures (SOP) for high alert drugs and the incidence of medication errors at Dewi Sri Karawang Hospital. This research uses descriptive analytic method with cross sectional approach. The technique of taking research samples using a total sampling of 57 nurses. The results were analyzed by Chi Square test and there was no significant relationship between respondent's age and the incidence of medication errors (P-Value = 0.910 and 95% CI), there was no significant relationship between gender and the incidence of medication errors (P-Value = 0.439 and 95% CI), there is no significant relationship between the level of education and the incidence of medication errors (P-Value = 0.863 and 95% CI), and there is a significant relationship between nurses' adherence to standard operating procedures (SOPs) for high alert drugs with the incidence of medication errors (P-Value = 0.000 and 95% CI). The recommendation in this study is that nurses as professionals pay more attention to compliance with a procedure at work to reduce the incidence of medication errors.